A Virtual-Reality Training Simulator for Cochlear Implant Surgery. (April 2019) - Jones, Blake; Rohani, Seyed Alireza; Ong, Nelson; Tayeh, Tarek; Chalabi, Ahmad; Agrawal, Sumit K.; Ladak, Hanif M.
Background and Objectives . Hearing loss is one of the most prevalent chronic conditions and can significantly impact an individual's quality of life.Cochlear implantation (CI) is a widely applicable treatment for severe to profound hearing loss, however CI surgery can be difficult for surgical trainees to master. Training environments that are safe, controlled, and affordable are needed. To this end, we present avirtual-reality (VR) cochlear implantsurgical simulator developed with a popular, commercial game engine. Method .Unity3D was used to develop the simulator and model the delicate instruments involved. High-resolution models of human cochleae were created from images obtained from synchrotron-radiation phase-contrast imaging (SR-PCI). The physical-realism of the simulator was assessed via a comparison with fluoroscopic images of an actual cochlear implant insertion. Different resolutions of cochlear models were used to benchmark the real-time capabilities of the simulator with the number of frames per second (FPS) serving as the performance metric. Results . Quantitative analysis comparing the simulated procedure to fluoroscopic imaging revealed no significant differences. Qualitatively, the behaviour of the inserted and simulated implants were similar throughout the entirety of the procedure. The simulator was able to maintain 25 FPS even when experiencing an artificially high computational load. Conclusion . VR simulators provide a new and exciting avenue to enhance current medical education. Continued use of widely available and supported game engines in the development of medical simulators will hopefully result in lowered costs. Preliminary feedback from expert surgeons of the simulator presented here has been positive and future work will focus on evaluating face, content and construct validity.